Catalytic Fast Pyrolysis of Lignin Over Mesoporous Y Zeolite Using Py-GC/MS - Lee, Hyung Won; Kim, Tae Hwan; Park, Sung Hoon; Jeon, Jong-Ki; Suh, Dong Jin; Park, Young-Kwon (AMER SCIENTIFIC PUBLISHERS, 2013)
The catalytic pyrolysis of lignin was carried out at 500 degrees C using pyrolysis gas chromatography/mass spectrometry. In-situ vapor cracking method, in which the vapor-phase products from the noncatalytic pyrolysis step were catalytically upgraded in the second step, was used. Mesoporous Y zeolite, which was synthesized from commercial zeolite Y (CBV720) using the pseudomorphic synthesis method, was used for the catalytic pyrolysis of lignin for the first time. Further, a representative mesoporous material, Al-MCM-41, was applied for the catalytic pyrolysis of lignin. The main products of the non-catalytic pyrolysis of lignin were phenolic compounds because lignin mainly comprises phenylpropane units. Catalytic upgrading of the non-catalytic pyrolysis products resulted in increased yields of low-molecular-mass phenolics, mono aromatics, and poly aromatic hydrocarbons (PAHs). The production of mono aromatics and PAHs was enhanced remarkably when the more acidic mesoporous Y zeolite was used. Conversely, the yield of alkoxy phenolics was higher when the less acidic Al-MCM-41 was used. With increasing mesoporous Y/lignin ratio, the yield of total phenolics decreased and that of light phenolics increased. The yields of mono aromatics and PAHs increased sharply with increasing mesoporous Y/lignin ratio.
Keywords: BIOMASS; SELECTIVITY; CHEMICALS; AROMATICS